## You are here

Homeproof of Brahmagupta's formula

## Primary tabs

# proof of Brahmagupta’s formula

We shall prove that the area of a cyclic quadrilateral with sides $p,q,r,s$ is given by

$\sqrt{(T-p)(T-q)(T-r)(T-s)}$ |

where $T=\frac{p+q+r+s}{2}.$

Area of the cyclic quadrilateral = Area of $\triangle ADB+$ Area of $\triangle BDC.$

$=\frac{1}{2}pq\sin A+\frac{1}{2}rs\sin C$ |

But since $ABCD$ is a cyclic quadrilateral, $\angle DAB=180^{\circ}-\angle DCB.$ Hence $\sin A=\sin C.$ Therefore area now is

$Area=\frac{1}{2}pq\sin A+\frac{1}{2}rs\sin A$ |

$(Area)^{2}=\frac{1}{4}\sin^{2}A(pq+rs)^{2}$ |

$4(Area)^{2}=(1-\cos^{2}A)(pq+rs)^{2}$ |

$4(Area)^{2}=(pq+rs)^{2}-cos^{2}A(pq+rs)^{2}$ |

Applying cosines law for $\triangle ADB$ and $\triangle BDC$ and equating the expressions for side $DB,$ we have

$p^{2}+q^{2}-2pq\cos A=r^{2}+s^{2}-2rs\cos C$ |

Substituting $\cos C=-\cos A$ (since angles $A$ and $C$ are suppplementary) and rearranging, we have

$2\cos A(pq+rs)=p^{2}+q^{2}-r^{2}-s^{2}$ |

substituting this in the equation for area,

$4(Area)^{2}=(pq+rs)^{2}-\frac{1}{4}(p^{2}+q^{2}-r^{2}-s^{2})^{2}$ |

$16(Area)^{2}=4(pq+rs)^{2}-(p^{2}+q^{2}-r^{2}-s^{2})^{2}$ |

which is of the form $a^{2}-b^{2}$ and hence can be written in the form $(a+b)(a-b)$ as

$(2(pq+rs)+p^{2}+q^{2}-r^{2}-s^{2})(2(pq+rs)-p^{2}-q^{2}+r^{2}+s^{2})$ |

$=((p+q)^{2}-(r-s)^{2})((r+s)^{2}-(p-q)^{2})$ |

$=(p+q+r-s)(p+q+s-r)(p+r+s-q)(q+r+s-p)$ |

Introducing $T=\frac{p+q+r+s}{2},$

$16(Area)^{2}=16(T-p)(T-q)(T-r)(T-s)$ |

Taking square root, we get

$Area=\sqrt{(T-p)(T-q)(T-r)(T-s)}$ |

## Mathematics Subject Classification

51-00*no label found*

- Forums
- Planetary Bugs
- HS/Secondary
- University/Tertiary
- Graduate/Advanced
- Industry/Practice
- Research Topics
- LaTeX help
- Math Comptetitions
- Math History
- Math Humor
- PlanetMath Comments
- PlanetMath System Updates and News
- PlanetMath help
- PlanetMath.ORG
- Strategic Communications Development
- The Math Pub
- Testing messages (ignore)

- Other useful stuff

## Recent Activity

new question: Prove that for any sets A, B, and C, An(BUC)=(AnB)U(AnC) by St_Louis

Apr 20

new image: information-theoretic-distributed-measurement-dds.png by rspuzio

new image: information-theoretic-distributed-measurement-4.2 by rspuzio

new image: information-theoretic-distributed-measurement-4.1 by rspuzio

new image: information-theoretic-distributed-measurement-3.2 by rspuzio

new image: information-theoretic-distributed-measurement-3.1 by rspuzio

new image: information-theoretic-distributed-measurement-2.1 by rspuzio

Apr 19

new collection: On the Information-Theoretic Structure of Distributed Measurements by rspuzio

Apr 15

new question: Prove a formula is part of the Gentzen System by LadyAnne

Mar 30

new question: A problem about Euler's totient function by mbhatia